Personalidade e estilo de liderança : um estudo com os técnicos de voleibol na Superliga - Magro, Jane Maria Remor (2009)
In high performance sport context Sport Psychology has become needed to the comprehension of sport in its plurality as a sociocultural phenomena, because arouses a concern with other aspects beyond purely modalities techiniques and tatics, such as personality and leadership styles existing inside the sport environment. Than main objective of the study was to investigate the relation between personality and leadership style of male volleyball coaches from teams participants of the Superliga 2007/2008. Participated on the study 14 coaches and 176 athletes. As instruments were used: Personality Factorial Inventory (PASQUALI; AZEVEDO; GUESTHI, 1997) and the Leadership in Sport Scale (CHELLADURAI, 1980), As for data analysis were used: Shapiro-Wilk, mean and standard deviations, Student's T test to dependent and independent variables and Pearson's correlation, adopting p<0,05. It was verified that the coaches showed a personality profile with high scores in the needs: deference, affiliation, performance and persistence; while the exhibition and aggression needs showed low scores. As for leadership profile, in coaches selfperception, training-instruction and reinforcement showed higher mean values and in last appeared the autocratic behavior. At athletes perception level, the coaches were perceived as training-instruction and reinforcement oriented and less autocratic oriented. In athletes' preference, the higher mean values were focused on traininginstruction and reinforcement behaviors, with the autocratic behavior showing the lower mean value. At each version comparison, statistically significant differences were found between coaches self-perception and athletes perception in traininginstruction and reinforcement (p=0,00). Also, statistically significant differences were found between coaches' self-perception and athletes preferences in reinforcement (p=0,02). Statistically significant differences were also found between athletes' perception and preference in training-instruction, social support and reinforcement (p=0,00) behaviors and in democratic orientation (p=0,01). The results for the Perason' correlation test showed a correlation between the personality profile and the coaches' leadership styles. Positive correlations were observed between intraception and afiliation and social support behaviors (0,61), in the need of order and reinforcement behavior (0,56) and in the authonomy need and the autocratic behavior (0,61). As the negative correlation was found between denegation need and traininginstruction behavior (-0,56), exhibition need and social support behavior (-0,52), heterosexuality need and democratic behavior (-0,59) and intraception need and autocratic behavior (-0,58). Coaches personality profile in G1 showed high scores in assistance, deference, affiliation, dominance, performance, persistence and change needs and low scores in caress, denegation, exhibition and aggression needs. G2 coaches, on the other hand, showed high scores in the needs of deference, affiliation and persistence and low scores in exhibition and aggression needs. As for leadership profile both groups showed training-instruction and reinforcement with higher mean values for self-perception and in last the autocratic behavior. At athletes' perception of G1 and G2 the behaviors perceived in their coaches were training-instruction, reinforcement, and the lowest was the autocratic behavior. G1 and G2 athletes' preferences revealed higher mean values than perceived in training-instructuin behavior, reinforcement and lower in autocratic behavior. In the comparison of coaches self-perception and athletes' perception in G1 no differences were found in any of the behaviors. Coaches' self-perception and athletes' preference in G1 showed statistically significant difference in the democratic behavior (p=0,04) and coaches' self-perception and athletes' perception in G2 showed difference in the reinforcement behavior (p=0,02). Statistically significant differences were also found between athletes' perception and preference in G1 for training-instruction behavior (p=0,03) and training-instruction, social support, reinforcement and democratic behaviors in G2 (p=0,00). In relation to coaches' self-perception no differences were found between G1 and G2 coaches' behaviors. The comparison of athletes' perception from G1 and G2 in relation to leadership styles evidenced statistically significant differences in all of the coaches' behavior: training-instruction (0,01), social support (0,02), reinforcement, democratic and autocratic (0,00). When compared the athletes' preference from G1 and G2, no statistically significant differences wasobserved in any behaviors. Pearson's correlation test between personality and coaches' leadership styles in G1 showed positive correlation between intraception need and social support behavior (0,99) and negative correlation between intraception need and autocratic behavior (-0,96). Coaches from G2 evidenced positive correlations between affiliation need and social support (0,65) and autonomy need and autocratic behavior (0,66). The negative correlations occurred between denegation need and democratic behavior (-0,66), exhibition need (-0,64) and aggression (-0,71) with reinforcement behavior. So it is concluded, superliga coaches have personality characteristics and leadership styles focused on a better team performance. Coaches and athletes showed ambition and hard work to perform difficult tasks, keeping high realization standards and finishing every task initiated dedicating themselves to the execution without measuring efforts. These aspects are also observed in semi-finals coaches and athletes.